PECULIARITIES OF PREGNANCY AND DELIVERY OUTCOMES IN WOMEN AT HIGH INFECTIOUS RISK - Баринов, Сергей Владимирович; Тирская, Юлия Игоревна; Кадцына, Татьяна Владимировна; Лазарева, Оксана Вячеславовна; Медянникова, Ирина Владимировна; Чуловский, Юрий Игоревич (Mother and Baby in Kuzbass, 2020)
Pregnant women with chronic genital and non-genital infections are at a high risk of infections pregnancy and postpartum complications. Preterm birth is one of the leading causes of obstetric and neonatal complications and occurs in one in nine women. Forty per cent of preterm births are considered to be caused by abnormal vaginal flora, and there is currently no consensus on the contribution of combined bacterial and viral infection. Aim – to assess the course of pregnancy and delivery in women with a high risk of infection and/or inflammatory conditions in pregnancy. Materials and methods. We performed a prospective controlled observational two-phase study in 417 pregnant women with a high risk of infectious pregnancy complications. In Phase 1, we evaluated the medical history, pregnancy and delivery course in 355 women with a high risk of infectious pregnancy complications. In Phase 2, we evaluated 62 women with a high risk of infectious pregnancy complications and preterm birth. The control group for immunological parameters included 18 healthy women with uncomplicated term delivery. Results. In women with a high risk of infectious complications, pregnancy was associated with recurrent threatened pregnancy loss (49.8 %), preterm premature rupture of foetal membranes (64.3 %), followed by prolonged oligohydramnios. Almost in one in two women (47.9 %), pregnancy resulted in the delivery of preterm, low-birth-weight neonates. One in three women (30 %) experienced uterine hypotony and bleeding after vaginal and Caesarean delivery. Almost a third of women (32.1 %) developed inflammatory complications postpartum, and more than half of complications (54.4 %) was observed in women giving birth prematurely. Vaginal and cervical cultures in women who experienced preterm birth were dominated by non-obligate pathogens. We observed persistence of the Herpesviridae family both in the cervical canal and uterine cavity, specifically the Epstein-Barr virus (17.2 %; 95% CI: 10 %; 26.8 %). Preterm birth was associated with a significant increase in the CD16+/CD56+ cells and reduction of the CD3+/CD8+ cells, increase of the pro-inflammatory cytokine levels and reduction in anti-inflammatory cytokines. Conclusions. Pregnancies in women with a high risk of infections and/or inflammatory conditions were associated with high rates of recurrent threatened pregnancy loss, preterm rupture of membranes and preterm delivery.